Application of the Whole Brain Teaching Method as an Effort to Improve Early Childhood Listening Skills - Salsabilla Rizkytanova Rahmadya; Edi Waluyo (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study was motivated by the findings of children who did not pay full attention to the teacher during learning activities at TK ABA 27 Semarang. This resulted in children not being able to understand information and simple commands given by the teacher. The improvement effort that can be done is by applying the whole brain teaching method in the learning process. So, this study aims to analyze the effectiveness of applying the whole brain teaching method to improve listening skills in early childhood. This study uses a quantitative approach with a one group pretest-posttest reasearch form, with a sample size of 12 children. From the results of the analysis that has been done using thet T-test formula, paired sample t-test with 95% significance, it is stated that the probability value is 0,00 which is < 0,05, it can be concluded that H0 is rejected and H1 is accepted, which means that the application of the whole brain teaching method has effectiveness in improving listening skills in early childhood at TK ABA 27 Semarang. The application of this method shows several positive findings, namely increasing focus, understanding of the material, creating a conducive and pleasant learning atmosphere, and fostering enthusiasm.